Induced Pluripotent Stem Cells Reveal Functional Differences Between Drugs Currently Investigated in Patients With Hutchinson‐Gilford Progeria Syndrome. (5th March 2014) - Blondel, Sophie; Jaskowiak, Anne-Laure; Egesipe, Anne-Laure; Le Corf, Amelie; Navarro, Claire; Cordette, Véronique; Martinat, Cécile; Laabi, Yacine; Djabali, Karima; de Sandre-Giovannoli, Annachiara; Levy, Nicolas; Peschanski, Marc; et al.
Abstract : Hutchinson‐Gilford progeria syndrome is a rare congenital disease characterized by premature aging in children. The results of this systematic comparative study of the three main treatments currently administered or proposed to progeria‐affected children reveal the complexity of the modes of action of different drugs and underscore the use of induced pluripotent stem cell derivatives as a critical and powerful tool for standardized, comparative pharmacological studies. Abstract : Hutchinson‐Gilford progeria syndrome is a rare congenital disease characterized by premature aging in children. Identification of the mutation and related molecular mechanisms has rapidly led to independent clinical trials testing different marketed drugs with a preclinically documented impact on those mechanisms. However, the extensive functional effects of those drugs remain essentially unexplored. We have undertaken a systematic comparative study of the three main treatments currently administered or proposed to progeria‐affected children, namely, a farnesyltransferase inhibitor, the combination of an aminobisphosphonate and a statin (zoledronate and pravastatin), and the macrolide antibiotic rapamycin. This work was based on the assumption that mesodermal stem cells, which are derived from Hutchinson‐Gilford progeria syndrome‐induced pluripotent stem cells expressing major defects associated with the disease, may be instrumental to revealing such effects. Whereas all three treatments significantly improved misshapen cell nuclei typically associated with progeria, differences were observed in terms of functional improvement in prelamin A farnesylation, progerin expression, defective cell proliferation, premature osteogenic differentiation, and ATP production. Finally, we have evaluated the effect of the different drug combinations on this cellular model. This study revealed no additional benefit compared with single‐drug treatments, whereas a cytostatic effect equivalent to that of a farnesyltransferase inhibitor alone was systematically observed. Altogether, these results reveal the complexity of the modes of action of different drugs, even when they have been selected on the basis of a similar mechanistic hypothesis, and underscore the use of induced pluripotent stem cell derivatives as a critical and powerful tool for standardized, comparative pharmacological studies.